2003
DOI: 10.1128/mcb.23.18.6520-6532.2003
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Retinoblastoma Protein Degradation by Interaction with the Serpin Plasminogen Activator Inhibitor 2 via a Novel Consensus Motif

Abstract: Plasminogen activator inhibitor-2 (PAI-2

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
95
2

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(105 citation statements)
references
References 48 publications
7
95
2
Order By: Relevance
“…PAI-2 A380 also lost its binding to HSP90/Beclin 1, resulting in loss of autophagy induction in response to LPS. However, residue 380 of PAI-2 is crucial for retinoblastoma stability and protection from TNF-induced apoptosis (12,32) . PAI-2 decreases IL-1β, but not TNF, production and cell death in response to E. coli infection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PAI-2 A380 also lost its binding to HSP90/Beclin 1, resulting in loss of autophagy induction in response to LPS. However, residue 380 of PAI-2 is crucial for retinoblastoma stability and protection from TNF-induced apoptosis (12,32) . PAI-2 decreases IL-1β, but not TNF, production and cell death in response to E. coli infection.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, PAI-2 has been associated with newly identified uPA-independent biological functions, probably through targeting an as yet uncharacterized intracellular molecule (11). In addition, PAI-2 is one of the major molecules up-regulated in macrophages in response to TLR4 activators or inflammatory mediators, suggesting its function in the regulation of innate immunity (12,13).…”
mentioning
confidence: 99%
“…However, it has been recently reported that in Hela and in Jurkat cells PAI-2 expression could result in post-transcriptional recovery of the retinoblastoma protein Rb, and that PAI-2 could inhibit Rb degradation, suggesting an intriguing intranuclear role of PAI-2. 11 Under physiological conditions, the expression of PAI-2 gene is maintained at low to undetectable levels in several cells. 3 However, it has been reported that a wide variety of factors, such as lipopolysaccharide, phorbol myristate acetate, tumor necrosis factor-a, interleukin-1, can modulate PAI-2 expression in different cell types.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the threedimensional structure of RB C-region in complex with an E2F/DP heterodimer has been reported (Rubin et al, 2005). The RB C-region also interacts with a Pro, Glu, Asn, Phe ('PENF') peptide motif found in several cellular proteins (Darnell et al, 2003), and a binding site for cyclin-dependent protein kinases (Adams et al, 1999). A majority of the RB-interacting proteins are regulators of transcription (Morris and Dyson, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Subsequent studies of RB C-region binding partners have led to the identification of a 'PENF' motif that is present in Abl, cPLA2, BRCA1, and several other cellular proteins as the motif recognized by the RB 'C-pocket' (Darnell et al, 2003). The 'PENF' motif is present in the Abl kinase domain, at the C-helix of the kinase N-lobe.…”
Section: Introductionmentioning
confidence: 99%